Promosi Kesehatan Tentang Literasi Kesehatan Kepada Pengunjung Puskesmas Guntung Manggis Kota Banjarbaru - Ludowika Adonita Tarong; Samsul Hadi; Fanli Yudi Anwar; Kunti Nastiti; Pertiwi Awilda; Sheila Nurrahmah; Bawaihi Bawaihi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Health is an optimal condition, both physical and spiritual, which enables a person to carry out all activities optimally without any obstacles. This situation can be realized by increasing health literacy. Health literacy is an individual's ability to understand health information and apply it in making appropriate health decisions. The aim of this health promotion is to provide information and knowledge to the public regarding health literacy so that the public can better understand the importance of having good health literacy in creating a healthy society. The method used is the lecture method using leaflet media. There were 11 participants in this activity, while the resource persons or presenters were PKPA students from Lambung Mangkurat University at the Guntung Manggis Health Center. Health promotion results obtained from the pretest and post-test results of 11 participating respondents showed an increase in understanding in all question items up to 100%. It is hoped that this increase in knowledge will influence people's behavior to further improve the health literacy of each individual.